DNA assisted synthesis of CeO2 nanocrystals with enhanced peroxidase-like activity - Wang, Meng; Mei-Fang, Wang; Yi-Ming, Wang; Ji-Wei, Shen; Zhi-Ying, Wang; Gao, Han; Li-Li, Wang; Ouyang, Xiangyuan (CrystEngComm, 2018)
A series of CeO2 nanocrystals with different sizes have been synthesized with DNA as the template by a hydrothermal synthesis method. The peroxidase-like activity of the CeO2 nanocrystals was found to be strongly enhanced by DNA doping.